2022
DOI: 10.3390/ijms23179905
|View full text |Cite
|
Sign up to set email alerts
|

The Flagellar Transcriptional Regulator FtcR Controls Brucella melitensis 16M Biofilm Formation via a betI-Mediated Pathway in Response to Hyperosmotic Stress

Abstract: The expression of flagellar proteins in Brucella species likely evolved through genetic transference from other microorganisms, and contributed to virulence, adaptability, and biofilm formation. Despite significant progress in defining the molecular mechanisms behind flagellar gene expression, the genetic program controlling biofilm formation remains unclear. The flagellar transcriptional factor (FtcR) is a master regulator of the flagellar system’s expression, and is critical for B. melitensis 16M’s flagellar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Each of these processes depends on different virulence factors regulated by specific genes to fulfill their functions. For instance, capsule polysaccharide synthetase Cap8J regulates capsule formation, and the flagellar synthesis regulator and CobQ/CobB/ MinD/ParA family play a pivotal role in polar flagella expression and virulence [29][30][31]. Studies have shown that a MinD mutant of Escherichia coli O157: H7 reduces its adhesion to human epithelial cells [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Each of these processes depends on different virulence factors regulated by specific genes to fulfill their functions. For instance, capsule polysaccharide synthetase Cap8J regulates capsule formation, and the flagellar synthesis regulator and CobQ/CobB/ MinD/ParA family play a pivotal role in polar flagella expression and virulence [29][30][31]. Studies have shown that a MinD mutant of Escherichia coli O157: H7 reduces its adhesion to human epithelial cells [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…An educational study conducted in India reported that after education, reduction in the risk behaviors practices like raw milk consumption, assisted animal delivery without gown, and throwing animal birth products in the dustbin were statistically significant. 26 An educational intervention based on the health belief model in Iran showed that after the educational program, the scores of awareness, perceived susceptibility and severity, self‐efficacy, and performance in the intervention group increased significantly. 13 This study was conducted only in livestock farmers, so it was not possible to compare with other demographic groups.…”
Section: Discussionmentioning
confidence: 99%